Whose experience matters in the boardroom? The effects of experiential and vicarious learning on emerging market entry. (24th April 2013) - Tuschke, Anja; Sanders, WM. Gerard; Hernandez, Exequiel
<x xml:space="preserve">Abstract</x> Using an organizational learning perspective, we develop arguments about vicarious learning through board interlocks and its relation to experiential learning. Although it is well established that firms learn from board interlocks, little attention has focused on which types of interlocks are most consequential and why. We distinguish between the relative advantages of various tie attributes such as experience, authority, and credibility and argue that these distinctions lead to measureable differences in learning outcomes. We further demonstrate that whether vicarious learning substitutes or complements focal firm experiential learning depends upon the type of interlock involved. After accounting for the endogeneity of ties, we find support for our framework in a longitudinal analysis of foreign investments by German firms in emerging economies between 1990 and 2003. Copyright © 2013 John Wiley & Sons, Ltd.